2012
DOI: 10.1103/physrevb.85.235446
|View full text |Cite
|
Sign up to set email alerts
|

Morphology transitions in bilayer spinodal dewetting systems

Abstract: In spontaneous pattern formation by spinodal dewetting, attractive intermolecular forces overcome surface tension and cause an ultrathin liquid film on a low energy substrate to produce ordered structures. Spinodal dewetting in single-layer film on a substrate, is usually manifested by an early stage surface deformation and a highly non-linear ripening stage that results in characteristic morphologies, typically bicontinuous-or hole-like states. Here we have experimentally constructed the dewetting morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Theoretically, h T for a single layer film is strongly correlated to the minima of the free energy curvature, which, in turn, is the second derivate of the thicknessdependent free energy of the film/substrate system. 7,13,42 The free energy G and its curvature for a single layer film on a substrate are given by 13,42 :…”
Section: Transition Thicknessmentioning
confidence: 99%
“…Theoretically, h T for a single layer film is strongly correlated to the minima of the free energy curvature, which, in turn, is the second derivate of the thicknessdependent free energy of the film/substrate system. 7,13,42 The free energy G and its curvature for a single layer film on a substrate are given by 13,42 :…”
Section: Transition Thicknessmentioning
confidence: 99%
“…This laser energy density also ensured minimal evaporation and/or ablation of the various metals and/or carbon film. As described in great detail in previous works, by controlling the number of pulses it is possible to obtain different morphologies of the single layer or bilayer films . Here, we made different Ag NSs by irradiation with 1, 50, or 100 pulses.…”
Section: Description Of Ns‐pldew and C Float‐off Processmentioning
confidence: 99%
“…As described in great detail in previous works, by controlling the number of pulses it is possible to obtain different morphologies of the single layer or bilayer fi lms. [ 14,20 ] Here, we made different Ag NSs by irradiation with 1, 50, or 100 pulses. For both the bilayer cases investigated, we applied 100 pulses to form nearly hemispherical-shaped NSs.…”
Section: Stage 1: Thin Film Deposition and Nanostructure Synthesismentioning
confidence: 99%
“…Note that (i) we include gravity terms in the pressures, since it has been shown that these terms may be important in a certain range of parameters [28,34], and (ii) we do not include the electronic component in the disjoining pressures [60], since for a single layer as well as for a bilayer system the inclusion of the electronic component does not result in the noticable improvement in matching of the theoretical predictions to the experiment, such as, for instance, the prediction of the critical film thickness at which the transition from bicontinuous structures to holes takes place [13,61]. The surface tension gradients, ∂ x σ 1,2 in Eqs.…”
Section: Evolution Equations For the Bilayermentioning
confidence: 99%